Arterial thoracic outlet syndrome in an adolescent - Shyam S Kothari; Bhavik Champaneri; Nirav Panchal (Wolters Kluwer Medknow Publications, 2023)
Arterial thoracic outlet syndrome (aTOS) is rarely diagnosed in children. A 15-year-old boy with recent-onset claudication was found to have aTOS on investigation. Bony abnormality other than the cervical rib might also cause aTOS. Enhanced awareness of aTOS as a cause of vascular symptoms in children is warranted.